Reward Processing in Motivational and Affective Disorders - Frank Ryan (Frontiers Research Topics, 2016)
Preferential reward processing is the hallmark of addiction, where salient cues become overvalued and trigger compulsion. In depression, rewards appear to lose their incentive properties or become devalued. In the context of schizophrenia, aberrations in neural reward signalling are thought to contribute to the overvaluation of irrelevant stimuli on the one hand and the onset of negative symptoms on the other. Accordingly, reward processing has emerged as a key variable in contemporary, evidence based, diagnostic frameworks, such as the Research Domain Criteria launched by the United States National Institute of Mental Health. Delineation of the underlying mechanisms of aberrant or blunted reward processing can be of trans-diagnostic importance across several neuropsychiatric disorders. Reward processing can become automatic thus raising the question of cognitive control, a core theme of this Topic, which aims at justifying the necessity of reward processing as a potential therapeutic target in clinical settings. Empirical and theoretical contributions on the following themes were expected to: *Explore new avenues of research by investigating the processing of rewards at the cognitive, behavioral, motivational, neural systems and individual difference levels. A developmental focus is promising in this regard, probing the core processes that shape reward processing and thus subsequent liability to motivational and affective disorders. *Develop and refine conceptual models of reward processing from computational neuroscience. *Promote greater understanding and development of emergent therapeutic approaches such as cognitive bias modification and behavioural approach or avoidance training. A key question is the feasibility of reversing or modifying maladaptive patterns of reward processing to therapeutic ends. *Refine and augment the evidential database for tried and tested therapies such as Contingency Management and Behavioral Activation by focusing on core cognitive processes mediating rewards. *Provide a potential dimensional approach for reward processing deficits that can be of trans-diagnostic importance in clinically relevant disorders, including depression and addiction * Investigate the subjective experience of pleasure- the hedonic aspect of reward seeking and consumption - and how this can be distinguished from the motivational, sometimes compulsive, component of reward pursuit. This promises more nuanced and effective interventions. Depression, for instance, could be seen as the restricted pursuit of pleasure rather than blunted pleasure experience; addiction can be viewed as accentuated drug seeking despite diminished consummatory pleasure. This aims to place motivation centre stage in both scenarios, emphasising the transdiagnostic theme of the Topic. *Temporal discounting of future rewards, whereby smaller, more immediate rewards are chosen even when significantly more valuable deferred rewards are available, is another trans-diagnostic phenomenon of interest in the in the present context. Factors that influence this, such as discounting of future reward are thought to reflect compulsion in the addictive context and hopelessness on the part of people experiencing depression. The executive cognitive processes that regulate this decision making are of both scientific and clinical significance. Empirical findings, theoretical contributions or commentaries bearing on cognitive or executive control were therefore welcome.